(untitled) (International Journal of Engineering and Computer Science, 2015)
This work presents the development of a mobile payment system which implements cashless economy using Nigeria as a case study. The main aim of this development is to reduce some cash-related crimes in our society such as: robberies, the risk of losing cash in the case of fire and flooding incidents, inefficiency and corruption associated with cash usage like leakages, money laundering, amongst other cashrelated fraudulent activities. The mobile payment system developed produces services operated under financial regulation and performed from or via a mobile device. With the use of this mobile payment system, instead of paying with cash or check, a consumer can use a mobile phone to pay for a wide range of services, digital or hard goods. This payment system is a service system where the consumer sends a payment request via an SMS text message to a customized code, the system evaluates the request with regards to financial regulations and either accepts the request and carries out the financial transaction or rejects the request by sending an SMS back to the consumer that sent the request. AT commands for VB.Net programming language is the tool used in the development of this mobile payment system with MySQL as the database.